2015
DOI: 10.1016/j.molcel.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Mn2+-Sensing Mechanisms of yybP-ykoY Orphan Riboswitches

Abstract: Summary Gene regulation in cis by riboswitches is prevalent in bacteria. The yybP-ykoY riboswitch family is quite widespread, yet its ligand and function remained unknown. Here we characterize the Lactococcus lactis yybP-ykoY riboswitch as a Mn2+-dependent transcription-ON riboswitch, with a ~30–40 μM affinity for Mn2+. We further determined its crystal structure at 2.7 Å to elucidate the metal sensing mechanism. The riboswitch resembles a hairpin, with two coaxially stacked helices tethered by a four-way junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
204
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(222 citation statements)
references
References 56 publications
(74 reference statements)
12
204
0
Order By: Relevance
“…Furthermore, each discovery links the riboswitch ligand to the protein products of the genes under regulation. Recent riboswitch findings have exposed unique facets of biology, such as the widespread molecular mechanisms that confer fluoride (5) or guanidine (6) resistance, that maintain metal ion homeostasis (7)(8)(9), and that control important bacterial processes such as sporulation, biofilm formation, and chemotaxis (10)(11)(12)(13)(14). Thus, the identification of additional riboswitch classes promises to offer insights into otherwise hidden biological processes and their regulation.…”
mentioning
confidence: 99%
“…Furthermore, each discovery links the riboswitch ligand to the protein products of the genes under regulation. Recent riboswitch findings have exposed unique facets of biology, such as the widespread molecular mechanisms that confer fluoride (5) or guanidine (6) resistance, that maintain metal ion homeostasis (7)(8)(9), and that control important bacterial processes such as sporulation, biofilm formation, and chemotaxis (10)(11)(12)(13)(14). Thus, the identification of additional riboswitch classes promises to offer insights into otherwise hidden biological processes and their regulation.…”
mentioning
confidence: 99%
“…One of the longest-unresolved orphan riboswitch candidates was the yybP motif RNA . After many years of uncertainty (Meyer et al 2011), both genetic (Dambach et al 2015) and structural (Price et al 2015) data eventually confirmed the hypothesis (Waters et al 2011) that members of this orphan riboswitch candidate naturally respond to Mn 2+ ions. A total of 4383 representatives of this riboswitch class have been identified in species from 18 divisions of bacteria, indicating that this riboswitch and its natural ligand are broadly important for bacteria.…”
Section: Five Distinct Riboswitch Classes Sense Atomic Ionsmentioning
confidence: 67%
“…These four families all possessed transmembrane regions with conserved charged amino acids, suggesting these could be manganese exporters. Of these, a previous study had suggested that the P-type ATPase might have a role in export of manganese in firmicutes (32). Both UPF0016 and TerC belong to the same higher-order clade of the LysE superfamily as MntP and share the conserved acidic residue in each of the core three-helical TM units (Fig 2).…”
Section: The Upf0016 Family Proteins Are Predicted To Be Novel Manganmentioning
confidence: 98%
“…In E. coli, the mntP gene has been shown to be transcriptionally and post-transcriptionally regulated by manganese levels through the MntR transcription factor and the yybP-ykoY riboswitch (20,31). The yybP-ykoY riboswitch directly and specifically binds manganese and regulates gene expression by ribosomebinding site sequestration or termination/antitermination mechanism in different organisms (31,32). Intriguingly, the yybP-ykoY riboswitch is very broadly conserved across bacteria, suggesting an important role for manganese homeostasis.…”
Section: Introductionmentioning
confidence: 99%